Kontribusi konsep diri akademik dan locus of control terhadap perencanaan karir siswa - Siti Fauziah; Marjohan Marjohan (JRTI (Jurnal Riset Tindakan Indonesia), 2022)
This research is constrained by the lack of students understanding phenomenon description in carrier planning after graduation from Senior High School 3 Padang. The academic self concept and locus of control are suspected factors affecting students career planning. The aims of this study are (1) to analyze the student’s career planning of the SMAN 3 Padang, (2) to analyze the student’s academic self concept of the SMAN 3, (3) to analyze the student’s locus of control of the SMAN 3 Padang, (4) to examine the contribution of academic self concept to the student’s career planning of the SMAN 3 Padang, (5) to examine the contribution of locus of control to the student’s career planning of the SMAN 3 Padang, (6) to examine the contribution of academic self concept and locus of control to the student’s career planning of the SMAN 3 Padang.  The research uses a quantitative method of descriptive type of correlation. The research population is 358 students, the amount of sample is 189 students. It was selected by proportional stratified random sampling technique. The instrument used is the scale of the likert model. The data are analyzed with descriptive statistics, simple regression, and multiple regression. The findings of the study showed that: (1) the description of planning of carrier is on high category, (2) the description of self academic self concept is on high category, (3) the description locus of control in the internal categories, (4) the academic self concept contributes to increasing of student’s career planning, (5) locus of internal control categories contributes to increased student’s career planning, (6) the academic self concept and locus of control contributes together on improving of student’s career planning. The implication of the result is able to become necessity analysis in Guidance and Counseling service and as a basic in conducting the program.